Characteristics of a New Plastic Explosive Named EPX-1 - Ahmed Elbeih (Journal of Chemistry)
EPX-1 is a new plastic explosive (in the research stage) which has been prepared for military and civilian applications. EPX-1 explosive contains pentaerythritol tetranitrate (PETN) with different particle size as explosive filler bonded by nonenergetic thermoplastic binder plasticized by dibutyl phthalate (DBP). In this paper, the production method of EPX-1 was described. The crystal morphology was studied by scanning electron microscope (SEM). Heat of combustion was determined experimentally. The compatibility of PETN with the polymeric matrix was studied by vacuum stability test. Sensitivities to impact and friction were measured. The detonation velocity was measured experimentally and the detonation characteristics were calculated by EXPLO5 thermodynamic code. For comparison, Semtex 1A, Semtex 10, Formex P1, and Sprängdeg m/46 were studied. It was concluded that PEX-1 has compatible ingredients, it has the highest detonation velocity of all the studied plastic explosives, and its sensitivity is in the same level of the studied plastic explosives except Semtex 1A.